Verifiable database outsourcing supporting join. (1st August 2018) - Etemad, Mohammad; Küpçü, Alptekin
Abstract: In an outsourced database scheme, the data owner delegates the data management tasks to a remote service provider who is supposed to answer owner's queries on the database. The essential requirements are ensuring the data integrity and authenticity with efficient mechanisms. Current approaches employ authenticated data structures to store security information, generated by the client and used by the server, to compute proofs that show the query answers are authentic. The existing solutions have shortcomings with multi-clause queries and duplicate values in a column. We propose a hierarchical authenticated data structure for storing security information, which alleviates the mentioned problems. Our solution handles many different types of queries, including multi-clause selection and join queries, in a dynamic database. We provide a unified formal definition of a secure outsourced database scheme, and prove that our proposed scheme is secure according to this definition, which captures previously separate properties: correctness, completeness, and freshness . The performance evaluation based on our prototype implementation confirms the efficiency of our proposed scheme, showing ∼3x smaller proofs and ∼5x improvement in proof generation time compared to previous works (Devanbu et al. 2002; Pang et al. 2005; Li et al. 2010; Palazzi et al. 2010).